A cycle time model for analysing the efficiency of working capital management in a value chain. (1st January 2013) - Viskari, Sari; Kärri, Timo
When technology already enables just-in-time operations and immediate financial transactions, financial supply chain management has emphasised the importance of financial flows and working capital management, which consist of the management of inventories, accounts receivable and accounts payable. However, the literature lacks concrete models and practices to control working capital, especially in the inter-organisational context. This paper introduces a working capital management (WCM) model for analysing the efficiency of working capital management at corporation level and for observing the financing cost caused by tied-up working capital in an inter-organisational value chain. The model emphasises the benefits of a new cycle time measure, the adjusted cash conversion cycle, when observing the inter-organisational context, and when calculating the financing cost. The WCM model was applied to a value chain of four companies in the automotive industry, a raw material supplier, a component supplier, a system supplier and a car manufacturer. A numerical example of the model with the data of financial statements is shown.